(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: This study seeks to investigate the potential relationship between fixed orthodontic appliances and sleep quality using the Pittsburgh Sleep Quality Index (PSQI). By examining the impact of orthodontic appliances on sleep, this research aims to contribute to our understanding of how orthodontic treatment may affect sleep quality. To investigate the effect of fixed orthodontic appliance on sleep quality in the patients attended at the department of Orthodontics using Pittsburgh sleep quality index. Materials and methods: This comparative cross-sectional study was carried out in the Department of Orthodontics. Patients who were taking fixed orthodontic treatment was enrolled in the study using simple random sampling method. Prior to the commencement of this study, ethical approval by the Institutional Review Board (IRB) of Bangladesh Medical University and Department of Orthodontic was taken. Descriptive statistics were calculated and one-samplet-test was used to compare PSQI global score. The cu-off point we used to determine poor sleep quality was >5. Comparison between males and females for PSQI was done using independent samples test. All of the statistical analyses were performed using specialized statistical software SPSS version 26(IBM SPSS Statistics for Mac, Version 26.0. Armonk, NY:IBM Corp.). Results: One hundred and sixty participants were included in the final analysis (46.25% males and 53.75% females). Both males and females with orthodontic fixed appliances had poor sleep quality with (Mean = 6.80, SD = 1.38) for males and (Mean=7.28, SD=1.40) for females. Comparing males and females, we found that females scored higher than males in both subjective sleep quality and PSQI global score. Conclusion: Individuals who has received fixed orthodontic appliance experienced decline in sleep quality. And female group showed poor sleep quality than male. JCMCTA 2025 ; 36 (2) : 137-140